1998
DOI: 10.1596/0-8213-4226-6
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Lines in Theory and Practice

Abstract: To present the results of the Living Standards Measurement Study with the least possible delay, the typescript of this paper has not been prepared in accordance with the procedures appropriate to formal printed texts, and the World Bank accepts no responsibility for errors. Some sources cited in this paper may be informal documents that are not readily available. The findings, interpretations, and conclusions expressed in this paper are entirely those of the author(s) and should not be attributed in any manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
174
1
31

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(208 citation statements)
references
References 34 publications
2
174
1
31
Order By: Relevance
“…There is a tradition, followed in both the United States and India, of setting poverty lines with reference to what Ravallion (1998) refers to as "the nutritional requirements for good health." This is defined as the level of income (or total consumption) at which, on average, nutritional norms are met.…”
Section: International Comparability Without Purchasing Power Paritymentioning
confidence: 99%
“…There is a tradition, followed in both the United States and India, of setting poverty lines with reference to what Ravallion (1998) refers to as "the nutritional requirements for good health." This is defined as the level of income (or total consumption) at which, on average, nutritional norms are met.…”
Section: International Comparability Without Purchasing Power Paritymentioning
confidence: 99%
“…Some are characterized by an assemblage of monetary and economic methods (Ravallion 1998, Laderchi 2000, Sachs 2005) and others use concepts such as access, entitlements, capabilities, and freedom to bring an institutional and political orientation to poverty (Sen 1981, Mearns 1996, Leach et al 1999. A number of frameworks are used in the literature, including sustainable livelihoods (Chambers and Conway 1992, Scoones 1998, Bebbington 1999, vulnerability (Blaikie 1994, Adger et al 2005, Allison and Horemans 2006, Marschke and Berkes 2006, social well-being (White and Ellison 2007, McGregor 2008, Bavinck 2009, Coulthard 2009, Trimble and Johnson 2013, Weeratunge et al 2013) and field-based, bottom-up and participatory tools to deal with social exclusion (Narayan et al 2000a, 2000b, Beck and Nesmith 2001, Laderchi et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…the old or disabled) and it also raises the moral question of the appropriateness of defining poverty in such an instrumental way. Ravallion (1998) has suggested that the poverty line should be defined as the "minimum cost of the poverty level of utility". Yet this does not get one much further as the concept of a "minimum level of utility" is itself not well-defined.…”
mentioning
confidence: 99%